2014
DOI: 10.1002/dev.21266
|View full text |Cite
|
Sign up to set email alerts
|

Maternal‐child adrenocortical attunement in early childhood: Continuity and change

Abstract: This study evaluated continuity and change in maternal-child hypothalamic-pituitary-adrenal axis attunement in early childhood. Participants were drawn from a prospective study of 1,292 mother–child dyads, which were racially diverse, predominantly low-income, and non-urban. Child focused stress tasks designed to elicit anger, fear, and frustration were administered during early infancy, later infancy, and toddlerhood. Mothers’ and children’s saliva samples (later assayed for cortisol) were collected before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 59 publications
(88 reference statements)
8
94
0
Order By: Relevance
“…A possible explanation is that maternal frontal asymmetry is contextual as previously claimed (Killen & Teti, 2012), but based on a history with the child and not solely on the “here and now” interaction. This supports recent findings related to cortisol, which proposed that adrenocortical attunement is a result of a combination of diurnal and momentary synchronicity (Hibel et al, 2015). Thus, children’s behavior is related to both baseline and task maternal frontal asymmetry.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A possible explanation is that maternal frontal asymmetry is contextual as previously claimed (Killen & Teti, 2012), but based on a history with the child and not solely on the “here and now” interaction. This supports recent findings related to cortisol, which proposed that adrenocortical attunement is a result of a combination of diurnal and momentary synchronicity (Hibel et al, 2015). Thus, children’s behavior is related to both baseline and task maternal frontal asymmetry.…”
Section: Discussionsupporting
confidence: 92%
“…However, there are studies that have assessed the association between child and parent physiological activity: One body of research investigated the coregulation of cortisol levels of children and parents during an interaction and revealed that maternal behavior and cortisol levels were associated with child’s adrenocortical activity (Granger, 1998; Hibel, Granger, Blair, & & Finegood, 2015). Additionally, Ruttle and colleagues (2011) provided evidence that mother-child dyads showed, overall, some systematic synchronization (“attunement”) of the hypothalamic-pituitary-adrenal (HPA) axis, which was particularly prominent during challenging tasks.…”
Section: Mother-child Interaction and The Role Of Emotional Regulationmentioning
confidence: 99%
“…Parental physical presence, parent's emotional expression, and parent's own physiological reactivity act as phasic modulators of child emotional and physiological reactivityregulating the child's internal experiences and behavioral output in different environmental contexts. This phasic regulation may have an important long-term function, helping to calibrate children's set point of emotional and physiological reactivity (Blair and Raver, 2012;Hibel et al, 2014a). In addition, tonic levels of parental care experienced in early life appear to alter rates of child emotional development.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of cortisol covariation are complex (Timmons, Margolin, & Saxbe, 2015). Within parent-child dyads, covariation might facilitate children’s self-regulatory capabilities (Feldman, 2007), and it has been associated with greater physical proximity and behavioral sensitivity (e.g., Hibel et al, 2015; Ruttle et al, 2011). However, the couples’ literature has more frequently found stronger covariation among distressed couples (Levenson & Gottman, 1983).…”
mentioning
confidence: 99%